Indolaminergic System in Adult Rat Testes: Evidence for a Local Serotonin System - Jiménez-Trejo, Francisco; Coronado-Mares, Isabel; Arriaga-Canon, Cristian; Herrera, Luis A.; Roque-Ramírez, Bladimir; Chávez-Saldaña, Margarita; Rojas-Castañeda, Julio; Cerbón, Marco; Vigueras-Villaseñor, Rosa M. (Frontiers in Neuroanatomy, 2021)
Serotonin (5-HT) integrate a family of indolamine molecules that are characterized for being an ancient molecule that participates in a wide variety of biological processes; 5-HT besides its important role in the regulation of local blood systems, currently, little is known about the physiological function of 5-HT on reproductive organs, its functional consequences, and its role in the reproduction of mammals. In the present work, we evaluate the localization and distribution of 5-HT (using histochemistry by indolamines) and different components of the serotoninergic system in the rat testes. We look if there a local synthesis and degradation through immunofluorescence and western blot against TPH1 and MAOA enzymes and 5-HTT and VMAT1 serotonin transporters. We also show localization and distribution of 5-HT1B, 5-HT2A, and 5-HT3A receptors. Some genes by RT-PCR: Tph1, Maoa, Slc6a4 and Htr3a present in both testes and brainstem except to Tph1 used as a negative control. Chromatographic analyses using HPLC documented the in vitro presence of 5-HT and activity of tryptophan hydroxylase in testes homogenates. Our observation suggests the presence of TPH1 activity in testes of rats and local serotonin synthesis. We think that the presence of this local serotoninergic system indicates that 5-HT could participate in the regulation of testosterone synthesis and spermatogenesis processes, along its putative role in both sperm maturation and fertilization processes in mammals. It is clear, however, that more studies are needed before concluding that rat testes and other mammals contain an active form of tryptophan hydroxylase and produce 5-HT.